Lichen planus and hepatitis C virus infection: An epidemiologic study - Tameez-ud-deen, Dr.; Naqqash, Shahzana; Butt, Abdul Quddus (Journal of Pakistan Association of Dermatologists, 2017)
Background Lichen planusÂ is an immunologically mediated skin and mucous membrane disease, which has been described in patients with hepatitis C virus-related liver disease, with variable frequency. Â Objective The purpose of this study was to determine the association of lichen planus with hepatitis C virus related liver diseases. Â Methods We tested sera of 55 patients with lichen planus for HCV antibodies by means of a second generation enzyme linked immunosorbent assay. Serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were simultaneously determined in all the patients. During the same period, a group of 110 patients admitted to the Dermatology Department, RGH, Rawalpindi, served as a control. Â Results Of the 55 patients with lichen planus, 18 had HCV antibodies (prevalence 32.7%), of the 110 control patients 8 had HCV antibodies (prevalence 7.2%). There was significant difference between the two groups. The ALT was raised in 21 patients with lichen planus, and 15 of them also had an elevated AST level. In the control patients, the AST level was raised in 4 of the 110 patients, 3 also had an elevated ALT level. The number of patients with an abnormal transaminase level significantly differed in the two groups (38.1% in the lichen planus group, and 4% in the control group). Â Conclusion These results support a possible relationship between LP and chronic hepatitis C and the hypothesis that LP may be associated with chronic liver diseases as a result of a cytotoxic attack on the hepatocytes. Â